Factorial Invariance of the 10-Item Connor-Davidson Resilience Scale Across Gender Among Chinese Elders - Meng, Meng; He, Jiayue; Guan, Yuzhu; Zhao, Haofei; Yi, Jinyao; Yao, Shuqiao; Li, Lezhi (Frontiers in Psychology, 2019)
Resilience plays an important role in the health of the elderly. The 10-item Connor-Davidson Resilience Scale (CD-RISC-10) is widely used to evaluate resilience, but its factorial invariance has not been evaluated in the Chinese elders. In the current study, 1,238 Chinese elders aged 60 years old and above completed the Chinese CD-RISC-10, yielding good reliability (Cronbach's α = 0.936 and test-retest reliability coefficient of 0.665 after 6 months). Confirmatory factor analysis indicated that a single-factor model fitted our CD-RISC-10 data well, both for the total sample and for each gender group. Furthermore, factorial invariance across genders was supported by multigroup confirmatory factor analysis. Finally, the current study revealed greater resilience levels in Chinese elderly women than in Chinese elderly men.